Daya Terima Modifikasi Ikan Sarden dan Sayur Bayam pada Dimsum Sebagai Makanan Tambahan Tinggi Kalsium - Manuntun Rotua; Sesiel K Putri; Podojoyo Podojoyo; Sriwiyanti Sriwiyanti (Pusat Unggulan IPTEK, Poltekkes Kemenkes Palembang, 2022)
Osteoporosis is a bone disease characterized by a decrease in bone density which causes bones to become brittle, bone conditions deteriorate where bone pores are porous. According to data from the Indonesian Ministry of Health, the prevalence of osteoporosis in 2016 there were 3,385 people who came to puskesmas with cases of Osteoporosis, consisting of 1,115 in men and 2,270 cases in women. From data from the Palembang City Health Office in 2017, there were 112 people who came to the South Sumatra Health Center with cases of osteoporosis, consisting of 37 men and 75 women. Strategies to overcome the problem by consuming foods that are high in calcium, such as milk, sardines, salmon, fish eaten with their bones (anchovies), soy-based foods, fruits, and green vegetables. The study was conducted using a non-factorial complete randomized design (RAL), using 30 untrained panelists. Acceptability is carried out by organoleptic tests. The results of the organoleptic test of dimsum selected in the F1 formulation (150 grams of sardines and 25 grams of spinach), the results of the acceptability test obtained an average color value of 3,567, aroma of 3.07, taste of 3.87, and texture of 3.47. The results of proximate analysis obtained an energy content of 203.74 kcal, protein 8.75%, fat, 1.82%, carbohydrates 38.09%, and calcium 96.42 mg.